Оценка информативности методики цифровой объемной томографии для диагностики состояния верхнечелюстных синусов (Эндодонтия Today)
Modern techniques of medical visualisation are a base of additional diagnostic and planning methods of surgical treatment in stomatology and maxillofacial surgery. Diagnosis of maxillary sinus perfomance is actual problem of oral and maxillofacial surgery, owing to prevalence of odontogenic sinusitis, and wide introduction of augmentation procedures in stomatologic practice. DVT (digital volume tomography) allows high resolution and contrast imaging of anatomic formations at rather low radiation loading and equipment cost. DVT technique has greater sensitivity (Se), specificity (Sp) and accuracy (Ac), than traditional methods of radiographic diagnostics (OPG and skull radiography in Waters projection).